Genomic and Functional Analyses of SXT, an Integrating Antibiotic Resistance Gene Transfer Element Derived from Vibrio cholerae - Beaber, John W. (American Society for Microbiology, 2002)
SXT is representative of a family of conjugative-transposon-like mobile genetic elements that encode multiple antibiotic resistance genes. In recent years, SXT-related conjugative, self-transmissible integrating elements have become widespread in Asian Vibrio cholerae. We have determined the 100-kb DNA sequence of SXT. This element appears to be a chimera composed of transposon-associated antibiotic resistance genes linked to a variety of plasmid- and phage-related genes, as well as to many genes from unknown sources. We constructed a nearly comprehensive set of deletions through the use of the one-step chromosomal gene inactivation technique to identify SXT genes involved in conjugative transfer and chromosomal excision. SXT, unlike other conjugative transposons, utilizes a conjugation system related to that encoded by the F plasmid. More than half of the SXT genome, including the composite transposon-like structure that contains its antibiotic resistance genes, was not required for its mobility. Two SXT loci, designated setC and setD, whose predicted amino acid sequences were similar to those of the flagellar regulators FlhC and FlhD, were found to encode regulators that activate the transcription of genes required for SXT excision and transfer. Another locus, designated setR, whose gene product bears similarity to lambdoid phage CI repressors, also appears to regulate SXT gene expression.